2017
DOI: 10.31406/relap2017.v11.i1.n20.3
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Mobility of Mexican Migrants in the United States

Abstract: In this paper we analyze the pre-to-post migration occupational mobility of Mexican migrants to the U.S. using occupation and migration histories from the Mexican Migration Project. We compare the first occupation in the U.S. to the last occupation in Mexico, and the occupation in the last year spent in the U.S. to the occupation in the first year, by sex, using multinomial logistic regression models. The multivariate analyses account for individual, migration, and context characteristics. Our findings show ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Although Mexican and Central American immigrants are thought to be negatively selected in terms of education (Borjas, 1987;Feliciano, 2005), recent research finds that, relative to those working in the same occupation, Mexican migrants are positively selected within their occupation (Villarreal, 2016). This is consistent with previous expectations of occupational mismatch among immigrants, whereby foreign workers often end up in jobs for which they are over-prepared (Sánchez-Soto and Singelmann, 2017;Villarreal and Tamborini, 2018;Sanroma et al, 2015). Besides the educational selectivity of immigrants, gender in-equality patterns in the labor market of the home country also influence the educational selectivity of female immigrants (Huh, 2017;Hoover and Yaya, 2010).…”
Section: Previous Researchsupporting
confidence: 70%
See 4 more Smart Citations
“…Although Mexican and Central American immigrants are thought to be negatively selected in terms of education (Borjas, 1987;Feliciano, 2005), recent research finds that, relative to those working in the same occupation, Mexican migrants are positively selected within their occupation (Villarreal, 2016). This is consistent with previous expectations of occupational mismatch among immigrants, whereby foreign workers often end up in jobs for which they are over-prepared (Sánchez-Soto and Singelmann, 2017;Villarreal and Tamborini, 2018;Sanroma et al, 2015). Besides the educational selectivity of immigrants, gender in-equality patterns in the labor market of the home country also influence the educational selectivity of female immigrants (Huh, 2017;Hoover and Yaya, 2010).…”
Section: Previous Researchsupporting
confidence: 70%
“…Previous research has found that immigrants are likely to experience no returns to their work experience prior to migration, and overall, human capital acquired in the place of origin is less likely to transfer to the place of destination (Ferrer and Riddell, 2008;Dell'Aringa et al, 2015;Perry, The return-on-education gap between hispanics and non-hispanic whites /G. SÁNCHEZ-SOTO et al 2017). However, the transferability of human capital is also dependent on the cultural proximity between the country of origin and destination.…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations